Synthesis and characterization of poly(hydroxamic acid) chelating resin from poly(methyl acrylate)-grafted sago starch - Lutfor, M. R.; Sidik, S.; Wan Yunus, W. M. Z.; Rahman, M. Z. A.; Mansor, A.; Haron, M. J. (John Wiley & Sons, 2001)
A new chelating ion-exchange resin containing the hydroxamic acid functional group was synthesized from poly(methyl acrylate) (PMA)-grafted sago starch. The PMA grafted copolymer was obtained by a free-radical initiating process in which ceric ammonium nitrate was used as an initiator. Conversion of the ester groups of the PMA-grafted copolymer into hydroxamic acid was carried out by treatment of an ester with hydroxylamine in an alkaline solution. The characterization of the poly(hydroxamic acid) chelating resin was performed by FTIR spectroscopy, TG, and DSC analyses. The hydroxamic acid functional group was identified by infrared spectroscopy. The chelating behavior of the prepared resin toward some metal ions was investigated using a batch technique. The binding capacities of copper, iron, chromium, and nickel were excellent and the copper capacity was maximum (3.46 mmol g-1) at pH 6. The rate of exchange of the copper ion was very fast that is, t1/2<5 min. It was also observed that the metal ion-sorption capacities of the resin were pH-dependent and its selectivity toward the metal ions used is in the following order: Cu2+>Fe3+ >Cr3+>Ni2+>Co2+>Zn2+ >Cd2+>As3+>Pb2+.